PERANCANGAN SISTEM INFORMASI BIDANG TANAH UNTUK OPTIMALISASI PENGELOLAAN ASET LAHAN DI PT KRAKATAU SARANA INFRASTRUKTUR - Anita Megayanti; Roy Amrullah Ritonga; Rizki Fatullah (Journal of Innovation And Future Technology, 2025)
The development of information and communication technology (ICT) has driven efficiency in data and information processing in various sectors, including the infrastructure industry. PT Krakatau Sarana Infrastruktur (KSI), as a company engaged in infrastructure management, faces challenges in managing data on land assets that have been acquired effectively. The complexity of operational activities and the geographical distribution of assets require an information system that is able to facilitate land management in an integrated and accurate manner.This study aims to design a land information system to optimize land asset management at PT KSI. The system development method used is the waterfall method, which allows system development to be carried out in a structured and systematic manner. System design is carried out by utilizing tools such as flowmaps, Unified Modeling Language (UML), and Entity Relationship Diagrams (ERD). The results of this study are in the form of a prototype information system that can present land data accurately and can be accessed by various related divisions at an optimal time. This system is expected to be able to increase the efficiency of information searches, reduce dependency between divisions, and support faster and more precise decision making in land asset management